Factors affecting cervical cancer knowledge among women in Addis Ababa, Ethiopia: A population-based study. - Ebrahim Mohammed Gebaba; Girma Taye Aweke; Adamu Addissie; Mathewos Assefa; Ahmedin Jemal (PLOS Global Public Health)
Cervical cancer (CCa) is the second leading cause of cancer-related death among women in Addis Ababa and other regions of Ethiopia. The aim of this study was to assess the level of awareness, knowledge, and knowledge of predictors of CCa and screening among women aged 30-49 years in Addis Ababa, Ethiopia. A total of 1980 women aged 30-49 were randomly selected through multistage sampling in Addis Ababa. Data were collected using the Kobo Toolbox after developing and validating the data collection tools. Data were analyzed using SPSS version 26. Logistic regression was used to identify predictors of cervical cancer awareness and knowledge, with a significance level set at a P-value of <0.05. Out of 1,890, 1,881 (99.5%) responded, 1,736 (92.3%) had heard of CCa, 1,015 (54.0%) were aware that Human Papillomavirus (HPV) infection is a risk factor, and 1,237 (65.8%) knew that HPV vaccination prevents CCa. More than half, 1,025 (54.5%) (95%CI = 52.2%-56.8%) had good knowledge of risk factors, 980 (52.1%) (95% CI = 49.8, 54.4%) had poor knowledge of symptoms, and 963 (51.2%) (95% CI = 48.9%, 53.5%) exhibited poor awareness. Overall, 990 (52.6%) (95% CI = 50.4, 54.9%) participants had good knowledge of cervical cancer. Factors such as higher educational attainment (AOR = 2.23; 95% CI: 1.49, 3.34), higher family income (AOR = 1.50; 95%CI: 1.01, 2.23), knowing health facility offering screening (AOR = 1.34; 95% CI: 1.07, 1.68), and knowing someone having cervical cancer (AOR = 5.46; 95% CI: 3.31, 8.97) were significantly associated with overall knowledge levels. Awareness and knowledge about cervical cancer and screening are suboptimal. These findings underscore the need for educational intervention to enhance awareness and knowledge of cervical cancer to reduce the high burden of the disease in the city and other regions of Ethiopia.